2021
DOI: 10.21203/rs.3.rs-1173983/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Voluntary HIV Counseling and Testing (VCT): Knowledge, attitudes, hinderances, and practices of adults seeking treatment at Gulu Regional Referral Hospital on the spread of HIV in Northern Uganda. A cross-sectional study

Abstract: Background: In 2011, Uganda had a national HIV prevalence of 6.7%. Between 2008 and 2009, there was an upsurge in HIV in Gulu District from 9.4% to 16.0% with Gulu Municipality at 22.1%. Similarly, in 2020, the prevalence of HIV in Gulu District persistently remained high at 14.0%, much higher than the national average at 6.0%.The objective of this study was to assess knowledge, attitudes, hindrances, and practices on voluntary HIV counseling and testing (VCT) and determine factors associated with VCT practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, we argue that the high prevalence of HIV and AIDs and cancers among females in Northern Uganda may have contributed to the higher mortality rates observed among the female COVID-19 patients in the current study population. Recent studies from Northern Uganda showed a higher prevalence of HIV and AIDS among females in Northern Uganda at 17.1% than males at 8.0% ( 34 ). Similarly, most cancer prevalence was higher in Northern Uganda than in the rest of the country, especially breast and cervical cancers which commonly affect females ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we argue that the high prevalence of HIV and AIDs and cancers among females in Northern Uganda may have contributed to the higher mortality rates observed among the female COVID-19 patients in the current study population. Recent studies from Northern Uganda showed a higher prevalence of HIV and AIDS among females in Northern Uganda at 17.1% than males at 8.0% ( 34 ). Similarly, most cancer prevalence was higher in Northern Uganda than in the rest of the country, especially breast and cervical cancers which commonly affect females ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from Northern Uganda showed a higher prevalence of HIV and AIDS among female gender in Northern Uganda at 17% compared to males at 9% [31]. Similarly, most cancer prevalence was higher in Northern Uganda than in the rest of the country, especially breast and cervical cancers [32].…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 98%